Ground beetles of the tribes Chlaeniini Brullé, 1834 and Rhopalomelini Alluaud, 1930 (Carabidae: Licininae) of Guinea-Bissau: description of two new species and faunistic notes - Serrano, Artur R. M. (Zootaxa, 2024)
Two new species of ground beetles of the genus Chlaenius Bonelli, 1810 (Coleoptera, Carabidae) from Guinea-Bissau are described: C. (Chlaeniostenus) kirschenhoferi n. sp. and C. (Chlaeniostenus) silvai n. sp., together with illustrations of their habitus and aedeagus. An annotated checklist of 20 species and subspecies of the tribes Chlaeniini and Rhopalomelini is provided, including data on general distribution, new country and new distribution records at country level. The list includes novel information from two entomological missions to that country carried out in 2006 and 2009 and also corrigenda data on previous published species. A new synonymy is established: Chlaenius (Paracallistoides) opisthographus Alluaud, 1934 is proposed as a junior synonym of Chlaenius (Chlaenius) zygogrammus LaFerté-Sénectère, 1851. Further, a dichotomic key is made available for the identification of the Guinea-Bissau species of Chlaenius (Chlaeniostenus) Kuntzen, 1919 subgenus. A historical review, as well as some considerations on the distribution and conservation status of these beetles in Guinea-Bissau is also presented.